Cognitive reserve in elderly: neuropsychological aspects and the education role in the latest findings - Dias, João Gabriel Magalhães; Silva, Pablo Rodrigo Andrade da; Alvez, Tânia Corrêa de Toledo Ferraz (Revista de Medicina, 2015)
The elderly population is growing worldwide, and therefore cognitive decline and dementia is a major problem for healthcare system. However, many elders do not develop dementia or significant cognitive impairment even though present brain lesions, such as cortical atrophy and/or lesions, leading to the concept of Cognitive Reserve (CR). The main objective of this review is to establish the recent findings of CR in elderly cognition and explore some of the cognitive markers related to CR. In order to accomplish that we carried out a search for papers published either in English or Portuguese language in the last 5 years in the Medline database using as keywords cognitive reserve, elderly and aging/ageing. We filtered 14 studies that specifically approached the neuropsychological aspects (e.g, memory, attention, orientation, executive function) and reviewed them in detail. Based on these papers regarding old-aged individuals, education appears to have several implications on CR by strengthening cognitive abilities, however does not appear to impact on cognitive decline. Besides, we realized that cognitive performance is one of the form to measure CR, even though the methods cannot be standardized, which may be the cause of some varied conclusions. Regarding CR, education was the most prevalent measure, and CR seems to have a beneficial effect on executive function and episodic memory and it seems to act by both neural reserve and neural compensation. Print exposure appears as a potential variable positively related to cognitive performance and CR.